The use of a metronome during cardiopulmonary resuscitation in the emergency room of a university hospital - Renata Maria de Oliveira Botelho; Cássia Regina Vancini Campanharo; Maria Carolina Barbosa Teixeira Lopes; Meiry Fernanda Pinto Okuno; Aécio Flávio Teixeira de Góis; Ruth Ester Assayag Batista (Revista Latino-Americana de Enfermagem)
ABSTRACT Objective: to compare the rate of return of spontaneous circulation (ROSC) and death after cardiac arrest, with and without the use of a metronome during cardiopulmonary resuscitation (CPR). Method: case-control study nested in a cohort study including 285 adults who experienced cardiac arrest and received CPR in an emergency service. Data were collected using In-hospital Utstein Style. The control group (n=60) was selected by matching patients considering their neurological condition before cardiac arrest, the immediate cause, initial arrest rhythm, whether epinephrine was used, and the duration of CPR. The case group (n=51) received conventional CPR guided by a metronome set at 110 beats/min. Chi-square and likelihood ratio were used to compare ROSC rates considering p≤0.05. Results: ROSC occurred in 57.7% of the cases, though 92.8% of these patients died in the following 24 hours. No statistically significant difference was found between groups in regard to ROSC (p=0.2017) or the occurrence of death (p=0.8112). Conclusion: the outcomes of patients after cardiac arrest with and without the use of a metronome during CPR were similar and no differences were found between groups in regard to survival rates and ROSC.